Optimalisasi Keamanan Informasi melalui Sistem Pengelolaan Surat yang Aman di Lingkungan Kerja - Lili Raflika; Khalisatun Husna; Muhammad Arby Fahrezi; Sari Andini; Saila Rahma Annisa; Tengku Darmansah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Mail management is a crucial element of organizational administration that plays a direct role in ensuring information security. This article discusses how poorly organized mail systems can create vulnerabilities for various threats to sensitive information, such as leakage, forgery, and document loss. Using a literature review method, the study identifies key risks and analyzes optimization strategies that can be implemented. The findings indicate that adopting digital systems, enhancing human resource (HR) capacity, and implementing access controls and audit trails are strategic steps to safeguard confidentiality, integrity, and availability of documents. The implications highlight the importance of integrating mail management with information security principles to establish an administrative governance system that is secure, efficient, and trustworthy.